Psychiatric Advance Directives: Benefits and Barriers - Scheyett, Anna (Current Psychiatry Reviews, 2008)
Psychiatric Advance Directives (PADs) are legal documents designed to allow individuals with serious mental illnesses (SMI) to continue to exercise choice in care during crises. PADs allow individuals with SMI to express their wishes for mental health care and to communicate relevant information regarding their condition at a future time when, because of SMI relapse, they may lack capacity and no longer be able to do so. PADs allow competent individuals to state preferences for mental health care through two mechanisms: advance instructions and health care power of attorney. Though medical advance directive legislation has existed since the 1980s, PAD legislation is newer, starting in the early 1990s. This review explores the literature addressing PADs, including the history and posited benefits of these documents. It examines the empirical literature on clinician attitudes towards PADs, the demand for PADs among individuals with SMI, the content of PADs that are developed, and their effectiveness during times of crisis. The review includes a discussion of the actions needed if PADs are to fulfill their promise as an effective tool to increase autonomy and decrease crises in persons with SMI. It concludes with recommendations on next steps for research in this field.
Keywords: serious mental illness